Conan O'Brien [videorecording (DVD)] : can't stop - O'Brien, Conan; Flender, Rodman, 1962-; Vivino, Jimmy; Healy, Scott; Merritt, Mike (Magnolia Home Entertainment, 2011)
After a much-publicized departure from hosting NBC's Tonight Show, O'Brien hit the road with a 32-city music and comedy show to exercise his performing chops and exorcise a few demons. An intimate portrait of an artist trained in improvisation, captured at the most improvisational time of his career. It offers a window into the private writers' room and rehearsal halls.